Subcritical water hydrolysis of industrial cake leftovers for sugar production - Mustapa Kamal, Siti Mazlina; Mohd Thani, Nurfatimah; Taip, Farah Saleena; Sulaiman, Alifdalino; Omar, Rozita (Springer, 2022)
Cakes are bakery goods that are frequently discarded. Cake leftovers are mostly carbs with a significant potential for sugar recovery using subcritical water hydrolysis; a clean, rapid, and sustainable approach. This study aimed to evaluate the highest sugar that could be recovered from cake leftovers using subcritical water hydrolysis. The cake leftovers were hydrolyzed in a batch-type subcritical water reactor at the process conditions of 160°C − 200°C, process time (5−15 minutes), and solid loading (10 − 50). The yields of total sugar and reducing sugar rose parallelly to the process conditions. The optimal process parameters for sugar recovery of the cake leftovers were 200°C, 15 minutes, and 50, yielding a total sugar yield of 0.895 mg/ml and a reducing sugar yield of 0.700 mg/ml. Hydrolysis of the carbohydrates resulted in sucrose, glucose, fructose, galactose, xylose, and mannose. Results from the scanning electron microscope (SEM) demonstrated that at higher temperatures (200℃), the surface of cake leftovers looked to be considerably changed. This study has set the framework for future research into the uses and benefits of subcritical water hydrolysis.